Particulate preplaced TIG melted surface layer of duplex stainless steel - Maleque, Md. Abdul; Afiq, M. (2017)
Despite their excellence qualities, DSS shows decrease in performance under aggressive environment. Under this condition, DSS is vulnerable to failure due to combined action of wear and corrosion. Therefore, the main aim of this project is to perform surface modification and study the effect of processing parameters in order to improve tribological properties of DSS. In this thesis, surface modification is done by using TIG Torch method where silicon carbide particles are fused into DSS substrate in order to form a new intermetallic compound at the surface. The effect of particles’ size, rate of particles’ preplacement, energy input and shielding gas flow rate on surface topography, microstructure, hardness and wear rate are investigated. Optimization on number of tests done based on the four parameters mentioned above is done by using Taguchi Method. Deepest melt pool (1.237 mm) is produced via TIG Torch with highest energy input which is at 1080 J/mm. Observations of surface topography shows rippling marks which confirms that re-solidification process has taken place. Melt microstructure consist of dendritic and globular carbides precipitate as well as partially melted silicon carbides particles. Micro hardness recorded at value ranging from 316 HV0.5 to 1277 HV0.5 which shows increment from base hardness of 260 HV0.5. The analysed result shows that incorporation of silicon carbide particles via TIG Torch method increase the hardness of DSS. As the hardness increases, wear resistance will also increase. Therefore, this improvement is useful in developing DSS with improved tribological.